PERBEDAAN KETERAMPILAN SOSIAL ANAK USIA DINI DITINJAU DARI POLA ASUH ORANG TUA DI TK AL BAROKAH PINANG MAKMUR KECAMATAN TIMPEH KABUPATEN DHARMASRAYA - isnaini, Isnaini (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2019)
The purpose of this research is to know the differences in children's social skills are reviewed from parents foster pattern in TK Al Barokah Pinang Makmur. This research method uses quantitative research, with the Cross Sectional research method. The population and research samples were 40 parents of students in TK Al Barokah. The main Data Collector tool uses a poll. A poll of the foster pattern is given to the elderly, while the social development questionnaire is given to the child. Based on the results of the study showed that the parents ' foster pattern in TK Al-Barokah Pinang Makmur is; 1) Democratic foster pattern with a percentage of 55%, of which there are as many as 22 respondents, where parents are also involved in decision making, parents prioritize child interest but still controlled, parents give freedom to the child to choose and do action, and parents do a warm approach with the child; 2) The authoritative foster patterns of 13 respondents with a percentage of 32.5%, here the child must be subject and obedient to the will of his parents, the control of parents to the behavior of children is strict and in communication is usually one-way; 3) Permissive parenting pattern is 10% with the number of respondents as many as 4 people, the pattern of foster like this means that parents give whatever children want; 4) The pattern of the study foster as much as 2.5% with the number of respondents 1 person. Patterns like this are not very good for the child, because it tends to let the child without good guidance and upbringing, the impact of this foster pattern the child will experience pressure both physically and psychic because the child does not get the attention and affection that the child should get.